2016
DOI: 10.3389/fpsyg.2016.00707
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Factor Model Better Explains Heterogeneity in Negative Symptoms: Evidence from the Positive and Negative Syndrome Scale

Abstract: Acknowledging separable factors underlying negative symptoms may lead to better understanding and treatment of negative symptoms in individuals with schizophrenia. The current study aimed to test whether the negative symptoms factor (NSF) of the Positive and Negative Syndrome Scale (PANSS) would be better represented by expressive and experiential deficit factors, rather than by a single factor model, using confirmatory factor analysis (CFA). Two hundred and twenty individuals with schizophrenia spectrum disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 42 publications
3
41
2
1
Order By: Relevance
“…In exploratory and confirmatory factor analyses, Liemburg et al (2013) found an “expressive deficit” (or expressive negative) subfactor that includes flat affect (N1 of the Negative PANSS items), poor rapport (N3), lack of spontaneity and flow of conversation (N6), mannerisms and posturing (G5), motor retardation (G7), and disturbance of volition (G13), and a “social amotivation” (or experiential negative) subfactor comprising emotional withdrawal (N2), passive/apathetic social withdrawal (N4), and active social avoidance (G16). This two-subfactor structure using PANSS negative item data from different patient samples was replicated by several other studies (Fervaha et al, 2014; Jang et al, 2016; Khan et al, 2017; Stiekema et al, 2016) confirming the same PANSS items for the social amotivation subfactor. For the expressive negative subfactor, PANSS items were the same across studies except for the PANSS disturbance of volition item (G13), which was included in only two studies (Liemburg et al, 2013; Stiekema et al, 2016), but not in the other three studies (Fervaha et al, 2014; Jang et al, 2016; Khan et al, 2017).…”
Section: Introductionsupporting
confidence: 71%
“…In exploratory and confirmatory factor analyses, Liemburg et al (2013) found an “expressive deficit” (or expressive negative) subfactor that includes flat affect (N1 of the Negative PANSS items), poor rapport (N3), lack of spontaneity and flow of conversation (N6), mannerisms and posturing (G5), motor retardation (G7), and disturbance of volition (G13), and a “social amotivation” (or experiential negative) subfactor comprising emotional withdrawal (N2), passive/apathetic social withdrawal (N4), and active social avoidance (G16). This two-subfactor structure using PANSS negative item data from different patient samples was replicated by several other studies (Fervaha et al, 2014; Jang et al, 2016; Khan et al, 2017; Stiekema et al, 2016) confirming the same PANSS items for the social amotivation subfactor. For the expressive negative subfactor, PANSS items were the same across studies except for the PANSS disturbance of volition item (G13), which was included in only two studies (Liemburg et al, 2013; Stiekema et al, 2016), but not in the other three studies (Fervaha et al, 2014; Jang et al, 2016; Khan et al, 2017).…”
Section: Introductionsupporting
confidence: 71%
“…hallucinations, blunted affect and formal thought disorder) on a scale ranging from 1 (‘absent’) to 7 (‘severe’) based on a semistructured interview. As both exploratory and confirmatory factor analyses have shown that MNS and ENS are separable factors in the PANSS, we calculated these as proposed in Fervaha and colleagues . Thus, we calculated the ENS factor from the PANSS items N1 Blunted Affect, N3 Poor Rapport, N6 Lack of Spontaneity, and G7 Motor Retardation.…”
Section: Methodsmentioning
confidence: 99%
“…avolition-asociality), a subdomain of negative symptoms, may impact social outcomes while expression of emotions (e.g. blunted affect) has a much reduced influence (Blanchard, 2006; Foussias, 2010; Harvey, Khan, & Keefe, 2017; Jang, 2016; Kring, 2013). Subdomains of IA: IA and IB of neurocognition preferentially predicts non-social everyday functional outcomes while IA and IB of social cognition most strongly predicts real-world social outcomes (e.g.…”
Section: Social Cognitive Iamentioning
confidence: 99%